DEVELOPING STUDENTS’ SPEAKING SKILL THROUGH IMPLEMENTATION OF ROLE-PLAY TECHNIQUE - Alfian Ferdian Tompunu; Rofiqoh Rofiqoh; Muhammad Arid (Tadulako University, 2021)
The objective of this research was to find out whether or not the implementation of Role-play technique can develop speaking skill. This quasi-research population was grade eleven students of MA Alkhairaat Pusat Palu. The sample was selected by using a random sampling technique. 19 Students from grade XI MIA 2 were taken as the experimental group and 19 students taken as control group. In order to assess students’ speaking skill, the researchers used speaking test. The students were asked some questions related to bullying and unhealthy food as pre-test and post-test. Based on the data analysis, the result of post-test showed the score of experimental group are better (71.68) in comparison to control group (65.77). From the result of the score deviation, the researchers continued using the result to find out t-counted using t-test formula. The result showed that the t-counted (2.89) is higher than the t-table (1.69). It indicates that the implementation of Role-play technique can develop speaking skill of the grade eleven students of MA Alkhairaat Pusat Palu.